INTEGRASI NILAI-NILAI QUR’ANI DALAM SISTEM EVALUASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMAN 1 MAKARTI JAYA - Ari Koswara; Fitria Hartati; Alimron; Suharmon (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe how Qur’anic values are integrated into the evaluation system of Islamic Religious Education (PAI) learning at SMAN 1 Makarti Jaya. Evaluation in the Islamic perspective does not merely assess students’ cognitive achievements but also encompasses affective and spiritual dimensions grounded in Qur’anic values such as justice (al-‘adl), responsibility (al-hisab), balance (al-wazn), and honesty (ash-shidq). The research employed a qualitative descriptive method with a field study approach. Data were collected through interviews with PAI teachers, classroom observations, and analysis of assessment documents. The findings reveal that PAI teachers at SMAN 1 Makarti Jaya have implemented Qur’anic-based evaluation principles through a continuous, fair, and character-oriented assessment system, which includes initial, formative, and summative evaluations. This implementation aligns with the values of tazkiyah an-nafs (self-purification) and hisab (accountability), indicating that evaluation functions not only as a measure of learning outcomes but also as a means of moral development. The study recommends strengthening teacher training programs to design evaluation instruments systematically based on Qur’anic values to enhance the spiritual and moral dimensions of education.